Insulin protects against type 1 diabetes mellitus-induced aortopathy associated with the inhibition of biomarkers of vascular injury in rats. (4th May 2021) - Bin-Jaliah, Ismaeel; Hewett, Peter W.; Al-Hashem, Fahaid; Haidara, Mohamed A.; Abdel Kader, Dina H.; Morsy, M. D.; Al-Ani, Bahjat
Abstract: Background: We sought to investigate the protective effect of insulin against type 1 diabetes mellitus (T1DM)-induced aortic injury (aortopathy) associated with the inhibition of biomarkers of vascular injury. Material and methods: T1DM was induced in rats by streptozotocin (STZ) (65 mg/kg), and the protection group started insulin treatment 2 days post diabetic induction and continued until being sacrificed at week 8. Results: Aortopathy was developed in the diabetic rats as demonstrated by profound alterations to the aorta ultrastructure, which was substantially protected by insulin. In addition, insulin significantly inhibited diabetes-induced dyslipidaemia, soluble vascular cell adhesion molecule-1 (sVCAM-1) and soluble intercellular adhesion molecule-1 (sICAM-1), oxidative stress, and inflammation. However, blood levels of these biomarkers in the insulin-treated group were still significant ( p < .05) compared with the control group, whereas insulin treatment returned blood glucose and triglyceride to control levels. Conclusions: We demonstrate effective protection by insulin against T1DM-induced aortopathy in rats, which is associated with the inhibition of vascular injury biomarkers.